Effect of Addition of Ecoenzyme on Trichoderma asperellum Formula Based on Black Glutinous Rice on the Root Growth of Sprouts of Bujang Marantau Rice Variety - Afyeni, Yutrin Nisya; Anhar, Azwir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Rice (Oryza sativa L.) is a staple food for Indonesians and plays a vital role in the country's economy. To increase rice production, intensification methods, including the use of fertilizers, are crucial. However, overuse of chemical fertilizers can damage soil structure and reduce microbial diversity. Organic fertilizers and biofertilizers, such as Trichoderma asperellum, have emerged as sustainable alternatives to chemical fertilizers due to their ability to produce growth-promoting hormones. This study investigates the effect of adding ecoenzyme to black glutinous rice-based Trichoderma asperellum formulas on the root length of Bujang Marantau rice variety seedlings. Using a Completely Randomized Design (CRD) with five treatments and five replicates, root growth was observed under varying concentrations of ecoenzyme (0%, 20%, 40%, 60%, and 80%). Results show that a 20% ecoenzyme concentration enhanced root length compared to the control. Higher concentrations, however, exhibited diminishing effects due to potential nutrient imbalances. The findings underscore the potential of ecoenzyme-enhanced Trichoderma asperellum formulations for sustainable agriculture.